Pengaruh Perputaran Kas, Perputaran Piutang Dan Pertumbuhan Perusahaan Terhadap Rentabilitas Ekonomi Pada Perusahaan Manufaktur Subsektor Makanan Dan Minuman Yang Terdaftar Di BEI - Susi Marni; Julisman; Surya Tegar Widjiantoro (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2021)
This study aims to determine whether the cash turnover, receivable turnover and corporate growth have an influence on rentabilitas in this study is represented by ROE. Based on the results of analysis using multiple linear regression method, f test and t test show that partially cash turnover, receivable turnover and corporate growth have no significant effect on profitability. This is evidenced by the significance value of cash turnover of 0.078 ˃ 0.05 and the significance value of receivable turnover of 0.457 ˃ 0.05. As well as the significance value of the company’s growth 0.981> 0.005 Similarly, the F test results or simultaneously obtained results that cash turnover, receivables turnover and corporate growth has no significant effect. This is evidenced by the value of significance F of 0.304 ˃0.05. R Square value of 0.090 which means that 9% of variability variables rentability. Cash turnover, receivable turnover and corporate growth can affect the amount of ROE by 9%, while the remaining 91% is influenced by other variables not examined in this research model.